Sijariemas (Sistem Informasi Jejaring Rujukan Expanding Maternal And Newborn Survival) di Kabupaten Bulukumba - Lukman Nul Hakim Amran Saputra; Hamrun Hamrun (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the implementation of innovative maternal and child health services through the SIJARIEMAS program in Bulukumba Regency. The type of research used in this study was qualitative research method. The data sources used were primary and secondary data sources, while the main problem is the higher MMR and IMR in Bulukumba Regency. The Data collection techniques used were interviews, observation and documentation. Data analysis techniques are through data collection, data reduction, data classification, data presentation, and drawing conclusions. The validity of the data was through source triangulation, technical triangulation, and time triangulation. The results of this study showed that the implementation of innovative maternal and child health services through the SIJARIEMAS program in Bulukumba Regency is quite good but still has obstacles in its implementation so that the government needs to optimize this program again.